Bacterial Enoyl-Reductases: The Ever-Growing List of Fabs, Their Mechanisms and Inhibition - Hopf, Fernanda S. M.; Roth, Candida D.; de Souza, Eduardo V.; Galina, Luiza; Czeczot, Alexia M.; Machado, Pablo; Basso, Luiz A.; Bizarro, Cristiano V. (Frontiers in Microbiology, 2022)
Enoyl-ACP reductases (ENRs) are enzymes that catalyze the last step of the elongation cycle during fatty acid synthesis. In recent years, new bacterial ENR types were discovered, some of them with structures and mechanisms that differ from the canonical bacterial FabI enzymes. Here, we briefly review the diversity of structural and catalytic properties of the canonical FabI and the new FabK, FabV, FabL and novel ENRs identified in a soil metagenome study. We also highlight recent efforts to use the newly discovered Fabs as targets for drug development and consider the complex evolutionary history of this diverse set of bacterial ENRs.